Exploring the influence of social environments on wellbeing in urban communities: A literature review and key indicators for future research - Hassan, Mohammad Mujaheed; Tedong, Peter Aning; Mohd Khir, Azlina; Shari, Zalina (Human Resource Management Academic Research Society (HRMARS), 2023)
In the rapidly urbanizing context, community well-being is vital for societal progress. Malaysia's growing urban landscape highlights the interplay between the social environment and urban community well-being. Amidst cultural diversity, where ethnicities converge, understanding the multifaceted social dynamics becomes pivotal. As traditions merge and languages harmonize, the social environment fosters unity and empathy. This study explores nuanced dimensions and their impact on urban well-being. Through an extensive scholarly review, it uncovers connections between sociodemographic, residential attributes, neighborhood dynamics, relationship support, community engagement, safety perceptions, identity, play, design, interaction variety, shared spaces, and outdoor opportunities. These facets shape urban life, influencing interactions and attachment. Malaysia's cultural tapestry emphasizes the social environment's role in harmonizing diverse communities, enhancing well-being, and resilience. Findings inform urban planning, policy-making, and community development, propelling inclusive and harmonious urban communities. Ultimately, this research underscores the social environment's potential as a catalyst for unity, contentment, and well-being in Malaysia's urban areas.